2021
DOI: 10.2196/19004
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Client-Psychologist Relationships in Videoconferencing Psychotherapy: Literature Review

Abstract: Background During the COVID-19 pandemic, people have been encouraged to maintain social distance. Technology helps people schedule meetings as remote videoconferencing sessions rather than face-to-face interactions. Psychologists are in high demand because of an increase in stress as a result of COVID-19, and videoconferencing provides an opportunity for mental health clinicians to treat current and new referrals. However, shifting treatment from face-to-face to videoconferencing is not simple: bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 73 publications
4
83
1
6
Order By: Relevance
“…In the paper "A Perspective on Client-Psychologist Relationships in Videoconferencing Psychotherapy: Literature Review" [15], the authors emphasize the prescience of this topic during the time of the COVID-19 pandemic. Suddenly, mental health therapy through digital means has become an imperative for many consumers, and so the quality of these therapies in establishing effective treatment has become a more urgent problem to solve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper "A Perspective on Client-Psychologist Relationships in Videoconferencing Psychotherapy: Literature Review" [15], the authors emphasize the prescience of this topic during the time of the COVID-19 pandemic. Suddenly, mental health therapy through digital means has become an imperative for many consumers, and so the quality of these therapies in establishing effective treatment has become a more urgent problem to solve.…”
mentioning
confidence: 99%
“…Participants in the study identified one of the benefits of blended therapy as strengthening the relationship between the client and the clinician, which is clearly important for DTA. It would be interesting to see this study extended to cover the views of therapists so that it could be compared to the findings of Cataldo et al [15].…”
mentioning
confidence: 99%
“…Despite therapists' concerns about the ability to develop a strong working alliance in online settings [41,42], research suggests that the working alliance in online psychotherapy is usually strong [43] and comparable to in-person therapies [44,45]. Although there is lack of research regarding the impact of the working alliance on online psychotherapy, the working alliance has been suggested to be crucial for good outcomes in online therapy via videoconferencing [46]. With regards to patients' attachments, individuals with a more secure attachment tend to report a stronger working alliance with their therapist, and more insecurely attached patients report a lower working alliance (for a meta-analysis, see [47]).…”
Section: Patients' Experiences Of the Collaborative Process In Therapymentioning
confidence: 99%
“…So deuten die Ergebnisse einiger Studien auch darauf hin, dass die therapeuteneingeschĂ€tzte Allianz im Rahmen der VB niedriger ist, als dies in Face-to-Face-Therapien der Fall ist (Cataldo et al. 2021 ; Rees und Stone 2005 ). Die Ursachen fĂŒr diese z. T. widersprĂŒchlichen Erfahrungen von Patienten und Therapeuten nĂ€her zu untersuchen, bleibt weiter von Bedeutung.…”
Section: Diskussionunclassified